2004
DOI: 10.1158/1055-9965.epi-03-0093
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Association between Prostate Cancer and the Use of Calcium Channel Blockers

Abstract: Calcium channel blockers block calcium signal-mediated apoptosis. It is hypothesized that the use of these drugs may be associated with the development of cancer. This study investigated the association between daily use of calcium channel blockers and prostate cancer in a community-based cohort of men who participated in a longitudinal study of lower urinary tract symptoms. Study subjects were men ages 40 to 79 years by January 1, 1990, and were randomly selected from Olmsted County in Minnesota. At baseline,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 27 publications
2
37
1
Order By: Relevance
“…Our findings of no association between BBs and prostate cancer are consistent with that seen in four [3][4][5]14] of six epidemiological studies [3][4][5][12][13][14]. In our study, use of BBs was associated with a statistically significant lower risk of prostate cancer in the age-race adjusted model, but the association was attenuated and not statistically significant in the multivariate model mainly due to adjustment by history of heart disease.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our findings of no association between BBs and prostate cancer are consistent with that seen in four [3][4][5]14] of six epidemiological studies [3][4][5][12][13][14]. In our study, use of BBs was associated with a statistically significant lower risk of prostate cancer in the age-race adjusted model, but the association was attenuated and not statistically significant in the multivariate model mainly due to adjustment by history of heart disease.…”
Section: Discussionsupporting
confidence: 89%
“…Several classes of drugs are commonly used individually or in combination as pharmacological treatment to prevent cardiovascular complications, including diuretics, beta-blockers (BBs), calcium channel blockers (CCBs), angiotensin-converting enzyme (ACE) inhibitors, and angiotensin II-receptor blockers. Eleven epidemiological studies have examined the association between anti-hypertensive treatment and risk of prostate cancer [3][4][5][6][7][8][9][10][11][12][13][14]. Results have been inconsistent for each class of anti-hypertensive drugs, but most of the studies had limited statistical power [4][5][6][7]10] or were unable to control for other prostate cancer risk factors [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, the study with the lowest risk of bias found no difference in LOS between the intervention and control participants. Consequently, while a reduction in prehabilitation-related reduction in LOS would be an important clinical finding given its positive association with re-admission rates, poor functional status and mortality, and negative association with healthcare costs [37,38], it is concluded that the overall evidence related to this outcome is equivocal. It is worth noting, however, that in the studies that observed reduced LOS [13,20,22], prehabilitation participants had better physical function and recovery [20], HRQOL [13] and peri-operative complications [22].…”
Section: Discussionmentioning
confidence: 99%
“…Less clear is the effect of calcium channel blockers in cancer, particularly prostate cancer. Thus, whereas some investigators report that the use of calcium channel blockers is inversely associated with prostate cancer (Debes et al, 2004), others have failed to find such a relationship (Rodriguez et al, 2009). Thus, it is of interest to investigate the potential effectiveness of these drugs in prostate cancer therapy, especially because both cardiovascular problems and prostate cancer are common in elderly men (Yoshinaga et al, 2006).…”
Section: Introductionmentioning
confidence: 99%